Hasil Perbandingan Pengasapan Ultra Low Volume Terhadap Aedes Aegypti Di Perumahan Dengan Lapangan Terbuka Menggunakan Insektisida Lorsban Dan Malathion - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT A trial of Lorsban 100 ULV and 150 ULV dosages of 250 ml/ha, 500 ml/ha, 1000 ml/ha and Malathion 96 EC dosage of 500 ml/ha against DHF vector Ae. aegypti. Fogging was conducted in the morning using Fontan Ultra Low Volume (ULV) in the residential and open area of Salatiga municipality in 1995. After 24 hours holding in the laboratory, the Air Bio assay test for all insecticides tested showed that spraying distance of 0 - 5 meters caused 100% Aedes aegypti mortality. There was no significant difference in Ae. Aegypti mortality between the residential and open area.